Implementasi Augmented Reality Sebagai Media Pengenalan Sistem Tata Surya Berbasis Android - Ardian Danang Kurniawan; Joko Aryanto (LPPM STIKI MALANG, 2024)
Most science subjects, especially those related to the solar system are still taught conventionally, using props such as books, blackboards, and props. These props do not attract the attention of students, so students become less interested in subjects. So it takes alternative media in the introduction of solar system materials. The purpose of this study is to create a solar system recognition application based on Augmented Reality. This application will make planetary objects more realistic and improve students ' understanding of the literature on the solar system. This research will use literature study research method. Identifying problems, conducting literature research, collecting data, developing systems, testing applications, and writing reports are the research steps. This research produces augmented reality applications that use markerless method so that 3D objects can be moved freely by the user. this application can be an alternative media introduction to the solar system, helping students gain a better understanding and encourage them to participate in active learning